International business : attitudes and alternatives / Alan Sitkin. - Sitkin, Alan (Routledge, 2022)
Expanding on issues of growing importance to global businesses including corporate social responsibility, corporate citizenship and sustainability, this new edition explores topics of great importance to business at the start of the new decade, including digital transformation and digital business, and explores the intersection of technology and pandemic-accelerated change to look to the future of business in a global setting.